Estimating Transpiration from Turfgrass Using Stomatal Conductance Values Derived from Infrared Thermometry - Kenton W. Peterson; D. Bremer; J. M. Blonquist Jr. (Kansas Agricultural Experiment Station Research Reports, 2017)
Infrared thermometry provides accurate measurements of plant canopy temperature, which, along with basic weather variables, allows estimation of canopy stomatal conductance to water vapor flux (gc) and transpiration. Using this method we compared modeled estimates of transpiration (CONDT) with evapotranspiration (ET) measurements from nearby microlysimeters (LYSET) in tall fescue (Schedonorus arundinaceusSchreb.) turfgrass. Results indicated transpiration may be reliably estimated via calculation of gcin turfgrass.
Keywords: Evapotranspiration; evapotranspiration models; water